1999
DOI: 10.1183/09031936.99.13107899
|View full text |Cite
|
Sign up to set email alerts
|

The bronchoprotective effect of inhaled salmeterol in preschool children: a dose-ranging study

Abstract: The optimal dose of salmeterol in infants and preschool children is not known. The aim of this study was to assess the bronchoprotective effect of different doses of salmeterol using methacholine-induced wheeze in children aged <4 yrs. Children <4 yrs old with a history of recurrent wheeze underwent two methacholine challenges within 7 days. One hour before each challenge they were pretreated in double-blind fashion using a metered-dose inhaler and Babyhaler spacer. Placebo was given before one challenge, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Formoterol and salmeterol have shown long-lasting bronchodilatory and bronchoprotective effects in preschool children [99,105]. There are no published double-blind randomised placebo-controlled trials in preschool children on the addition of long-acting inhaled b 2 -adrenergic agents to ICSs.…”
Section: Long-acting Inhaled B 2 -Agonistsmentioning
confidence: 99%
“…Formoterol and salmeterol have shown long-lasting bronchodilatory and bronchoprotective effects in preschool children [99,105]. There are no published double-blind randomised placebo-controlled trials in preschool children on the addition of long-acting inhaled b 2 -adrenergic agents to ICSs.…”
Section: Long-acting Inhaled B 2 -Agonistsmentioning
confidence: 99%
“…Other authors have favoured measuring the transcutaneous oxygen tension (tcPO 2 ), arguing that it is effort independent, reliable and repeatable and is superior to tracheal auscultation [3±5]. The methodology of the study by WILSON et al [4] involved cessation of challenge when tcPO 2 fell by 20%, which may have censored the PCW data.As part of a dose-ranging study of inhaled salmeterol in preschool children [6], the current study set out to reevaluate these two challenge endpoints. The aim of the study was to compare the sensitivity and safety of using audible wheeze and tcPO 2 in a methacholine challenge in children <4 yrs of age.…”
mentioning
confidence: 99%
“…As part of a dose-ranging study of inhaled salmeterol in preschool children [6], the current study set out to reevaluate these two challenge endpoints. The aim of the study was to compare the sensitivity and safety of using audible wheeze and tcPO 2 in a methacholine challenge in children <4 yrs of age.…”
mentioning
confidence: 99%
“…Weinstein et al 18 reported a trend to greater bronchodilatation with 42 µg than with 21 µg salmeterol in 243 children but found no statistically diVerent changes between the two doses. Primhak et al 19 did show additional bronchoprotective eVect against methacholine induced wheeze with an increase in a single salmeterol dose from 25 to 100 µg, but this was in younger children using a mask and spacer. It is diYcult to compare airway deposition with this device and a dry powder device.…”
Section: Discussionmentioning
confidence: 99%